An improved synthesis of the C42–C52 segment of ciguatoxin 3C. Issue 14 (4th April 2018) - Saito, Takafumi; Fujiwara, Kenshu; Sano, Yusuke; Sato, Takuto; Kondo, Yoshihiko; Akiba, Uichi; Ishigaki, Yusuke; Katoono, Ryo; Suzuki, Takanori
Graphical abstract: Highlights: Development of a practical synthetic route to the C42–C52 segment of ciguatoxin 3C. Stereoselective construction of the vicinal dimethyl branching at C47–48. One-pot, three-step cyclization of an epoxyester to form a γ-hydroxy δ-lactone. Abstract: In our previously reported method for the construction of the IJKLM-ring of ciguatoxin 3C (CTX3C), the lengthy synthetic process for the intermediate C42–C52 (L-ring) segment was problematic. Therefore, a new and improved procedure for the C42–C52 segment, having modified protecting groups, was developed. The new route includes a chirality transferring Ireland-Claisen rearrangement for the construction of the vicinal dimethyl branching at C47–48, a one-pot cyclization process for the establishment of the stereocenters at C45 and C46 as well as the γ-hydroxy δ-lactone framework corresponding to the L-ring, and Brown's asymmetric crotylboration for the installation of the stereocenters at C43 and C44. The new C42–C52 segment was successfully coupled with the previously reported C32–C41 (I-ring) segment to produce the IJKLM-ring.